Topic Modelling of Merdeka Belajar Kampus Merdeka Policy Using Latent Dirichlet Allocation - Thamrin, Sri Astuti; Rezki, Nurul; Siswanto, Siswanto (Department of Statistics ITS, 2024)
Topic modeling is the process of representing the topics discussed in text documents. In the current era of internet technology development, digital data is growing increasingly large, including tweet data from Twitter. This research aims to obtain topic modeling related to the Merdeka Belajar Kampus Merdeka policy on Twitter, which has been classified into positive and negative sentiments. The topic modeling method used is Latent Dirichlet Allocation (LDA). This method is for summarizing, clustering, connecting, or processing data from a list of topics. The data used in this research are tweets with the keyword